ETIOLOGY, PATTERNS AND TREATMENT MODALITIES FOR MAXILLOFACIAL FRACTURES - Muhammad Asif Shahzad; Momin Ayub Marath (ziauddin University, 2024)
Background: Over the years, the epidemiology of maxillofacial fractures keeps changing and new trends in etiology, pattern of presentation and management are constantly evolving. This, therefore, necessitates a constant appraisal of these fractures injuries in order to keep abreast with recent developments and changing pattern of their management. The aim of this study was to determine the frequency, etiology, patterns and different treatment modalities for maxillofacial fractures in patients treated at Lahore Medical and Dental College/Ghurki Trust Teaching Hospital (LMDC/GTTH). Methods: This cross sectional descriptive study was carried out at Lahore Medical and Dental College/Ghurki Trust Teaching Hospital (LMDC/GTTH) from February 2014 to October 2017.A total of 161 patients having maxillofacial fractures were included in the current study. Data on patients, including age, gender, cause of injury, fracture site, pattern and treatment modalities were collected and analyzed using SPSS version 20. Results: The age range was 3 to 62 (mean/SD, 26.42±11.24) with peak frequency occurring in age group 21-30 years. The male to female ratio was 5.2:1. The most common cause of maxillofacial fractures was road traffic accident (RTA) in 134 (83.23%) of patients, followed by in fall 12 (07.46%) and assault in 09 (05.59%) patients. The most frequent bone fractured was the mandible, which accounted for 117 (72.67%) cases and parasymphysis (43.22%) was the most frequent site affected, followed by 67 (41.61%) cases of zygomatic complex fracture and 56 (34.78%) cases of maxillary fractures. Open reduction and internal fixation (ORIF/ORIF with IMF) was performed in 127(78.88%) of patients while closed reduction and indirect fixation (IMF with eyelet wiring/arch bar elastics & splint fixation) was done in 34 (21.12%) of patients. Conclusion: As evidenced by the present study, majority of fractures were caused by RTA in 21-30 age group with male predominance. Mandible was the predominant fractured bone followed by the zygomatic complex area. ORIF was treatment of choice in the current study. According to present study, it seems reasonable to recommend that road traffic legislation enforcement and continuous public education towards the use of restraining devices and helmets should be encouraged by relevant authorities.